Observação versus relato de mães e professoras sobre competência social e comportamentos problemáticos em pré-escolares - Dias, Talita Pereira (2010)
The literature has produced evidence that: (a) the early assessment and intervention in social skills can prevent and overcome problematic behaviors; (b) in the case of assessment, there are limits and advantages to different procedures generally used as well as a consensus about the importance of the multimodal design; (c) studies that investigate the relation among data obtained using different procedures, such as observation and informants reports are still scarce, mainly, with preschoolers; (d) analyzes of convergences and divergences between informants reports and between different procedures can produce important information to plan intervention to promote social skills and reduce problem behaviors in the childhood. In this way, the present study had as objectives: (1) To verify similarities and differences in the assessment of social competence with comparisons among four groups of children (with good social skills repertoire - SSB; with internalizing problematic behaviors - IPB, externalizing - EPB e mixed - MPB) in each kind of assessment (mother s report, teacher s report and observation) and comparing the three kinds of assessment to each group; (2) To characterize convergences and divergences between different informants and procedures, with comparisons among groups and intragroups. Based on a sample of 152 children evaluated by Preschool Kindergarten Behaviors Scales (PKBS), 26 children were selected and distributed to each one of the groups. These children participated in five structured situations that were recorded and analyzed by judges previously trained. In the interviews, mothers and teachers reported how the children s performance in each structured situation would have been. The data were analyzed by descriptive and non-parametric inferential statistics. The results indicated that: (1) to each group, the evaluation of social competence by mother s and teacher s reports and by observation were consistent; (2) only the teacher s evaluation differentiated the groups - the children of CHS group presented the best scores of social skills and the CPI group, the worst scores; (3) the convergences between report s data and of observation, in general, were the highest in the CHS group and the lowest in CPI group, except to comparison between mother report and observation, with the most convergence to CPE group. Possible reasons to explain the lowest convergence in the group CPI are highlighted, and methodological, clinical and educational implications are discussed, suggesting plans of intervention based on these results.